The effects of creativity shape exercise in measuring the creative mental imagery level among form 1 student / Nik Syazwani Nik Azman - Nik Azman, Nik Syazwani (2013)
This study examines the creative mental imagery level between genders, among form 1 students. The 4 research questions were (a) is there any significance difference on creativity level in use creative shape exercise among gender (b) is there any significance difference on creative imagery level among gender (c) is there any significance factor influence creative in the mental imagery level and (d) is there any significance factor influence creative in the mental imagery level. The target population for this study was among form one students. Female student is from Sekolah Menengah Convent Sentul, Kuala Lumpur and male student from Sekolah Menengah Segambut Jaya Kuala Lumpur. The variables in this study are creativity, gender and mental imagery. Primary data used was the instruments vividness of Visual Imagery Questionnaire (WIQ) and creative shapes exercise the X ’s or O’s. After all the data were collected, they were analyzed by using SPSS (originally, Statistical Package for the Social Sciences). Finding which emerged from this study is female scored higher overall on creative mental imagery level compare than male. Researcher is hoping that this review will be useful to teachers in identify level of creativity among their students and can be used to enhance the teaching and learning process.